2002
DOI: 10.1016/s1074-7613(02)00325-4
|View full text |Cite
|
Sign up to set email alerts
|

Salp15, an Ixodes scapularis Salivary Protein, Inhibits CD4+ T Cell Activation

Abstract: Tick saliva has pleiotropic properties that facilitate persistence of the arthropod upon the host. We now describe a feeding-inducible protein in Ixodes scapularis saliva, Salp15, that inhibits CD4(+) T cell activation. The mechanism involves the repression of calcium fluxes triggered by TCR ligation and results in lower production of interleukin-2. Salp15 also inhibits the development of CD4(+) T cell-mediated immune responses in vivo, demonstrating the functional importance of this protein. Salp15 provides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
279
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 239 publications
(286 citation statements)
references
References 47 publications
4
279
1
2
Order By: Relevance
“…The C-terminal portion of Salp15 (amino acids 95-114 of the mature protein named P11, with the sequence GPNGQTCAEKNKCVGHIPGC - [17]) mediates its interaction with sCD4 [18] and recapitulates the immunosuppressive activity of Salp15 [26]. We thus tested the ability of purified P11 to compete CD4-gp120 binding.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The C-terminal portion of Salp15 (amino acids 95-114 of the mature protein named P11, with the sequence GPNGQTCAEKNKCVGHIPGC - [17]) mediates its interaction with sCD4 [18] and recapitulates the immunosuppressive activity of Salp15 [26]. We thus tested the ability of purified P11 to compete CD4-gp120 binding.…”
Section: Resultsmentioning
confidence: 99%
“…His-tagged Salp15 and Salp15ΔP11 were purified using the Drosophila expression system (DES), as described [17]. Recombinant HIV-1 IIIB HRP-conjugated gp120 and sCD4 (domains D1D2) were purchased from Immunodiagnostics, Inc. (Woburn, MA).…”
Section: Recombinant Proteins and Synthetic Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent genetic study showed that the midgut protein TROSPA is a receptor for OspA binding, whose presence enhances colonization by B. burgdorferi [170]. The salivary gland protein Salp15 is immunosuppressive and may facilitate infection by the low numbers of spirochetes that are transmitted during tick feeding [171,172]. Recently, a tick antioxidant was shown to facilitate tick acquisition of spirochetes from infected animals [173].…”
Section: B Burgdorferi Infection Of Ticksmentioning
confidence: 99%
“…We have recently cloned and characterized an immunomodulatory protein present in Ixodes scapularis saliva, Salp15, which is the first I. scapularis protein known to be associated with the immunosuppressive activity of tick saliva (1). Salp15 has been shown to impair proliferative responses of anti-CD3-plus anti-CD28-activated CD4 ϩ T cells by inhibition of T-cellreceptor-mediated calcium mobilization (1).…”
mentioning
confidence: 99%